LIKARI (Five Words in A Day) Application to Improve Vocabulary Mastery in Japanese Language Learning - Kartika, Diana; Oslan Amril; Tienn Immerry; Aulya Chasovy; Arief Juneirul Pratama (Journal for Lesson and Learning Studies, 2023)
Students experience several obstacles in understanding and mastering Japanese vocabulary. Students need to have appropriate and exciting strategies for learning vocabulary. Therefore, this research aims to develop interactive learning media using an Android-based application called "Likari." This application has a specific goal of using a method of mastering five Japanese vocabulary words in a day. This research uses Research and Development (R&D) research using the Borg & Gall development model. Data collection methods use observation, questionnaires, and tests. Field trials were conducted on a small scale on 34 class XI students. The experts involved in this research were 2 material experts and 2 media experts. The techniques used to analyze data are qualitative descriptive analysis, quantitative, and inferential statistics. Research shows that the "Likari" application is suitable or valid for school learning. The research results show that media experts assessed the implementation at 92%, and material experts rated it at 87%. The application is also included in the convenient category with a score percentage of 92%. Using the "Likari" application effectively improves students' mastery skills in learning Japanese, where the N gain score is 73.76%.